Vertical permeability between vocational and higher education: a case study of a Qatar technical institute's role in facilitating transition to higher education for trades students. (2nd September 2017) - Gamar, Samah Abdulhafid
Abstract: Education sectors worldwide have been pressed to re-evaluate admission and credit transfer policies to enhance higher education (HE) qualifications access and career mobility. This study presents the case of a technical institute's re-development of its vocational programme to facilitate academic credit transfer and establish accessible, efficient pathways to further and HE. It considers political and operational dimensions of this in an institution within the Middle East and North Africa region – where, as in many countries, technical vocational education and training (TVET) has been historically and culturally stigmatized. This analysis reveals that the TVET–HE divide can be bridged, and lifelong learning avenues promoted, through institutional policy and procedural reforms that transcend variant education and training delivery models to account for acquired competence. Opportunities for credential advancement and career mobility can be strategically broadened when mechanisms for the recognition and transference of learning acquired in vocational programmes are in place.